Impact of centrifugation and vacuum filtration step on the yield and molecular weight distribution of protein hydrolysates from rapeseed and sunflower meals. (1st August 2022) - Sentís-Moré, Pau; Ortega-Olivé, Nàdia; Mas-Capdevila, Anna; Romero-Fabregat, Maria-Paz
Abstract: The aim of this work was to produce protein hydrolysates directly from oilseed meals using an innovative and scalable extraction process, involving vacuum filtration in the solid/liquid step recovery. The protein hydrolysates produced were compared with those from the conventional centrifugation step. Such parameters as enzyme type, temperature and pH were also studied. The results suggest that the vacuum filtration process produced protein hydrolysates with higher weight yield, protein content, and protein yield than the centrifugation process in both studied meals, with higher values of 55.56% on weight yield for rapeseed meal; and 57.61 g/100 g on protein content and 71.87% on protein yield for sunflower meal. The protein fraction was also influenced by the extraction process, with a higher degree of hydrolysis, reaching a high value of 20.51% on filtration process of rapeseed meal, and lower molecular weight distribution in the protein hydrolysates from the vacuum filtration process, achieving the same angiotensin-converting inhibition activity as the protein hydrolysates from the centrifugation process. The vacuum filtration process was applied to study the fat content effect in a sunflower press cake, and no significant differences were stated in comparison with sunflower meal. Graphical abstract: Image 1 Highlights: Protein hydrolysates were obtained by applying the enzymolysis hydrolysis directly to the by-products. Vacuum filtration was studied as novel process for recovering protein hydrolysates. The proposed new operational unit of vacuum filtration improves yields values. The fat content of oilseed press-cake does not interfere on protein hydrolysates extraction results.